2021
DOI: 10.1111/1756-185x.14185
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis management in the APLAR region: Perspectives from an expert panel of rheumatologists, patients and community oriented program for control of rheumatic diseases

Abstract: Rheumatoid arthritis (RA) is a major health burden in Asia Pacific affecting the quality of life of patients and consuming healthcare resources. According to recent estimates from the World Health Organization‐International League Against Rheumatism‐Community Oriented Program for Control of Rheumatic Diseases, prevalence is around 0.3%‐0.5%. Management guidelines have helped to improve treatment across this diverse region. To gain better insight into current real‐world management applications in view of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…This principle has been significantly improved over the past few years. We have successively published the Asia‐Pacific guidelines or consensus recommendation articles for osteoarthritis, rheumatoid arthritis, lupus erythematosus, spondyloarthritis, gout, and other diseases 1‐13 . During the coronavirus disease 2019 (COVID‐19) pandemic, we have also published many practical guidelines, especially for the Asia‐Pacific region 10‐13 .…”
Section: Year Name Affiliation Photomentioning
confidence: 99%
See 1 more Smart Citation
“…This principle has been significantly improved over the past few years. We have successively published the Asia‐Pacific guidelines or consensus recommendation articles for osteoarthritis, rheumatoid arthritis, lupus erythematosus, spondyloarthritis, gout, and other diseases 1‐13 . During the coronavirus disease 2019 (COVID‐19) pandemic, we have also published many practical guidelines, especially for the Asia‐Pacific region 10‐13 .…”
Section: Year Name Affiliation Photomentioning
confidence: 99%
“…We have successively published the Asia-Pacific guidelines or consensus recommendation articles for osteoarthritis, rheumatoid arthritis, lupus erythematosus, spondyloarthritis, gout, and other diseases. [1][2][3][4][5][6][7][8][9][10][11][12][13] During the coronavirus disease 2019 (COVID-19) pandemic, we have also published many practical guidelines, especially for the Asia-Pacific region. [10][11][12][13] Those important articles have improved education research and clinical care quality in rheumatic diseases in Asia-Pacific regions.…”
mentioning
confidence: 99%
“…In Chinese patients, the prevalence of PsA is approximately 10%,4 5 although this could be underestimated in the Asia-Pacific region as patients with musculoskeletal disorders are often subject to delays in diagnosis. Other challenges that patients in this region experience include delayed or limited access to treatment with advanced therapies 5 6. Furthermore, due to limited access to information, patients may seek treatment to improve pain and disability, including traditional Chinese medicines, rather than treating signs and symptoms of inflammatory arthritis, further delaying treatment with advanced therapies 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Other challenges that patients in this region experience include delayed or limited access to treatment with advanced therapies 5 6. Furthermore, due to limited access to information, patients may seek treatment to improve pain and disability, including traditional Chinese medicines, rather than treating signs and symptoms of inflammatory arthritis, further delaying treatment with advanced therapies 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have indicated that the level of RF decreases more strongly than does the anti-CCP level, suggesting a greater plasticity or a different cellular origin of RF with effective treatment [4]. However, the optimal clinical use of anti-CCP and RF tests is unclear [1,4,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%